Psychometric properties of the Chinese version of the fathers’ fear of childbirth scale: A cross-sectional study - Pingping Guo; Pingping Guo; Xuehui Zhang; Nianqi Cui; Dandan Chen; Lijuan Wang; Qiong Zheng; Qiong Zheng; Jin Xu; Yin Jin; Minna Mao; Minna Mao; et al. (Frontiers in Psychiatry, 2023)
Background and AimFear of childbirth (FOC) is one of the most common mental health concerns among expectant fathers, which can cause adverse consequences for themselves and their families. A valid and accurate tool is the key to the identification of FOC. This study aimed to translate and culturally adapt the fathers’ fear of childbirth scale (FFCS) into simplified Chinese and test the scale’s psychometric properties among expectant fathers in mainland China.MethodsResearchers obtained translation permission and followed the multiphase translation guidelines to develop the Chinese version of the fathers’ fear of childbirth scale (C-FFCS). Relevant psychometric properties were selected for the scale’s psychometric validation on the basis of the Consensus-based Standards for the Selection of Health Status Measurement Instruments checklist. In this cross-sectional study, two samples of expectant fathers were collected in a university-affiliated hospital in Hangzhou between September and October 2022.ResultsA total of 381 expectant fathers completed the C-FFCS, resulting in an effective response rate of 95.6%. The C-FFCS is a 3-factor structure consisting of 16 items, which explained 66.374% of the total variance. The content validity index of items ranged from 0.833 to 1.00, and the scale-level content validity index was 0.931. The confirmatory factor analysis confirmed the scale’s 3-factor structure. Evidence of convergent validity (average variance extracted = 0.508–0.780) as well as discriminant validity offered excellent psychometric support. The Cronbach’s α coefficient, McDonald’s ω coefficient, intraclass correlation coefficient, Spearman-Brown coefficient, and Guttman split-half coefficient are within the satisfactory range (> 0.80). Significant correlations between the scores of the C-FFCS and Childbirth Attitude Questionnaire (r = 0.658, p < 0.01) and Fear of Birth Scale (r = 0.555, p < 0.01) both revealed good concurrent validity. The structure of C-FFCS was invariant across different parity groups, with no floor and ceiling effect.ConclusionThe C-FFCS was demonstrated to be a sound instrument with good reliability and validity for measuring Chinese expectant fathers’ FOC levels. However, further studies are advocated to verify the C-FFCS among a larger sample that is more representative of the Chinese expectant father population.